Study on the Dynamic Response of Gravel Soil Low Embankment under a Long-Time Dynamic Loading Based on Model Test - Dapeng Liu; Jing Wang; Feng Du (Advances in Materials Science and Engineering)
The low embankment is an important technique for road development in subgrade engineering due to its small fill height and applicability to the natural landscape in the oasis desert area of Xinjiang, China. A reasonable development of the gravel soil low embankment design requires the study of its dynamic response under a long-time dynamic loading. In the paper, a 1 : 1 full-scale low embankment model was established and tests of 100000 loading cycles with 50 kN peak value were carried out, taking into account three kinds of foundation moisture contents: 18%, 23%, and 28%. The test results show that the dynamic stress in the gravel soil low embankment attenuates nonlinearly with the increase in depth. The dynamic stress at each depth is the smallest for the water content value of 28% in the foundation. The stress attenuation rate is inversely proportional to the loading cycles and directly proportional to the water content of the foundation. The dynamic stress and dynamic strain in the gravel soil low embankment show cumulative effects with an increase of the loading cycles. The rate of stress and strain accumulation is faster for low loading cycles. The strain accumulation effect of each structural layer in the foundation is the largest for the water content value of 28%. The strain accumulation rate at the top layer of the foundation reaches 2.648. Based on the model test results, the dynamic stress calculation model for the gravel soil low embankment under dynamic loading is proposed. The calculation model was experimentally verified. The research results are important for the application of gravel soil low embankment in the oasis desert area of Xinjiang, China.